Aqueous Electrochemical Activity of the Mg Surface: The Role of Group 14 and 15 Microalloying Elements. Issue 13 (9th November 2017) - Yuwono, Jodie A.; Birbilis, Nick; Liu, Ruiliang; Ou, Qingdong; Bao, Qiaoliang; Medhekar, Nikhil V.
Abstract : Comparatively little is known about the aqueous electrochemical characteristics of magnesium (Mg) alloyed with group 14 and 15 elements. A combined analysis of theoretical and experimental studies was used to evaluate the role of such alloying elements in Mg surface reactions. The surface work function and surface hydroxylation reaction enthalpies were calculated, and the surface Pourbaix diagrams were constructed using first principles calculations. Group 14 and 15 elements exhibit the ability to restrict the water splitting and surface hydroxylation reaction upon Mg, thus providing an insight into their ability to suppress cathodic activation of Mg. Experimental studies using polarization, immersion testing, electrochemical impedance spectroscopy (EIS) and Raman spectroscopy verify a decreased electrochemical activity of Mg-0.3 Ge and Mg-0.3 Sb alloys, compared to that of pure Mg. The approaches presented here provide a means by which a metallurgical alloying can be used as a valuable mechanism for controlling Mg surface activity with beneficial implications for various applications of Mg.